2022
DOI: 10.3390/su14148646
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Revisit Intention towards Religious Attraction of Kartarpur Temple: Moderation Analysis of Religiosity

Abstract: This study examines the effect of destination image, cultural contact and perceived risk on revisit intention of Sikh pilgrims to Kartarpur temple, mediated by tourist satisfaction. The literature has debated the moderating effect of religiosity in a different tourism context. However, studies rarely investigate the moderating role of religiosity in the relationship of destination image, cultural contact and perceived risk with tourist satisfaction. This study follows a cross-sectional approach and self-admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 103 publications
(177 reference statements)
0
6
0
1
Order By: Relevance
“…Therefore, it is not surprising that financial behavior mediates financial attitudes towards financial performance. Previous research also agrees on the relationship between financial behavior and religiosity (Rehman et al, 2022). Financial attitude in particular can be interpreted as a feeling that supports or does not support based on certain preferences for financial objects (Ajzen, 2005) but other researchers understand financial attitude as a psychological tendency that is expressed in financial activities (Amanah et al, 2016).…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, it is not surprising that financial behavior mediates financial attitudes towards financial performance. Previous research also agrees on the relationship between financial behavior and religiosity (Rehman et al, 2022). Financial attitude in particular can be interpreted as a feeling that supports or does not support based on certain preferences for financial objects (Ajzen, 2005) but other researchers understand financial attitude as a psychological tendency that is expressed in financial activities (Amanah et al, 2016).…”
Section: Discussionmentioning
confidence: 72%
“…However, empirical investigations are still needed to assess and understand the experiences of visitors to a sacred place (Bideci and Bideci, 2022). Rehman et al (2022) revealed the moderating impact of religiosity among Sikh pilgrims that strengthens the association between "destination image, cultural contact, perceived risk, and satisfaction". According to Abror et al (2021), REL considerably moderates the impact of Muslim-friendly tourism on visitor satisfaction.…”
Section: Religiosity As Moderatormentioning
confidence: 99%
“…MTE was assessed using the four-item scale adopted from previously validated studies (Tiwari et al, 2023;Vada et al, 2019). MRE was measured using a five-item scale (Kamath et al, 2023) and REL was measured on 4 items (Barnard et al, 2017;Rehman et al, 2022). Also, ATT has been measured on 4 items (Hasan et al, 2019;Hsu and Huang, 2012) and BI (RCI) using 4 items (Mittal et al, 2021;Rasoolimanesh et al, 2022).…”
Section: Data Collection and Instrumentmentioning
confidence: 99%
“…Destination Type [14,19] Honeymoon tourism [8,10,15,18,30] Natural tourism [10,16,27] Culture tourism [17,20] Rural tourism [21] Yoga tourism [22,24] Urban tourism [23,29] Religious tourism [11] Health tourism [28] Event tourism of various factors found in tourism destinations that attract travelers to choose these destinations. On the other hand, according to [31], destination attributes refer to the factors that influence a traveler's decision to select one destination over another after the decision to travel has been made.…”
Section: Researchersmentioning
confidence: 99%